HARMONIZATION OF ASEAN LAW IN SOLVING ENVIRONMENTAL ISSUES FOCUSING ON ENVIRONMENTAL IMPACT ASSESSMENT LAW IN THAILAND - Amnat Wongbandit (Universitas Bengkulu, 2018)
As the ASEAN Economic Community was formed, in principle there should be a free flow of economic activities, capital, labor and other things across borders within this community for the benefit of all in the region but in reality, there are still some legal impediments to the achievement of this goal. Harmonization of law of ASEAN countries would help to ease this problem. The same is also applicable to the problems of environmental protection as different laws in different jurisdictions could lead to the situation that polluters would certainly try to stay away from a country with strict environmental law and move their business to where the law is not that strict, or law enforcement is quite weak.Environmental impact assessment has played a very important role in environmental protection because it can be used as a method to predict what would be an environmental consequence of carrying out particular project or activity and offer how negative impacts could be prevented or mitigated. This article therefore would like to present the environmental impact assessment law in Thailand which consists of several interesting issues that could be the subjects of debate as to whether it would be possible or practical to harmonize ASEAN laws on such issue